Accuracy of Optic Nerve Sheath Diameter Measurements in Pocket-Sized Ultrasound Devices in a Simulation Model - Johnson, Garrett G. R. J.; Jelic, Tomislav; Derksen, Angela; Unger, Bertram; Zeiler, Frederick A.; Ziesmann, Markus T.; Gillman, Lawrence M. (Frontiers in Medicine, 2022)
Introduction: Transorbital sonographic measurement of optic nerve sheath diameter (ONSD) is an emerging non-invasive technique for identification and monitoring of intracranial hypertension. In recent years, new pocket ultrasound devices have become available and it is uncertain if they have the resolution to measure such small structures appropriately as compared to their predecessors. In this study, we measure the performance of three ultrasound units on a simulation model to establish their precision and accuracy. Methods: ONSD was measured by three expert point-of-care sonographers using ultrasound machines three times on each of seven discrete ONS model sizes ranging from 3.5 to 7.9mm. Two pocket ultrasounds (IVIZ, Sonosite, and Lumify, Philips) and one standard-sized portable ultrasound (M-Turbo, Sonosite) were used. Measurements were analyzed for mean error and variance, and tested for significance using blocked covariance matrix regression analyses. Results: The devices differed in their variances (Lumify: 0.19mm2, M-Turbo: 0.26mm2, IVIZ: 0.34mm2) and their mean error (Lumify: -0.05mm, M-Turbo: 0.10mm, IVIZ: -0.10mm). The difference in mean error between users is not significant (p=0.45), but there is a significant difference in mean error between devices (p=0.02). Conclusions: Accurate ONSD measurement is possible utilizing pocket-sized ultrasound, and in some cases may be more accurate than larger portable ultrasound units. While the differences in these devices were statistically significant, all three were highly accurate, with one pocket device (Lumify) outperforming the rest. Further study in human subjects should be conducted prior to using pocket ultrasound devices for in vivo diagnosis of intracranial hypertension.